How Different is The Financial Performance of Sharia-Based Banks? - Listiana Sri Mulatsih; Mahelan Prabantarikso; Hadi Purnomo; Loso Judijanto; Alfiana (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
Covernance, Earnings and Capital. Based on the research results, it shows that there is a significant difference between Bank Muamalat Indonesia and Bank Mega Syariah in 2018-2021 in the Risk Profile factor based on the NPF ratio and there is no significant difference based on the FDR ratio. There is a significant difference between the average BMI and BMS in the Earnings factor based on the ROA ratio. A gap was found between the average values ​​obtained by BMI and BMS regarding the capital factor based on the CAR ratio and there was no significant difference between the financial performance of Bank Muamalat Indonesia and Bank Mega Syariah using the RGEC method.  The policy implication of these findings is the importance of viewing a bank's financial performance holistically, not just focusing on one factor such as capitalIn making policy decisions, regulators and bank management must consider these aspects comprehensively to enhance the overall health and performance of the bank.